Generalized Robinson and Marshall-Lerner Conditions With Positive Import Content of Exports. The Case of Two Countries - Fritz Breuss (Austrian Institute of Economic Research (WIFO), 1985)
The ROBINSON and MARSHALL-LERNER conditions are necessary and sufficient for a devaluation to be successful end are therefore the backbone of the elasticities approach to the balance of payments. These conditions are generalized by taking into account some actual features of modern foreign trade: positive import content of exports end the local content issue. In view of these effects, studied in a two country, two goods context, it can be concluded that a devaluation is likely to be less successful under given price elasticities. These results are of particular relevance for small open economies (SMOPECs). – The ROBINSON and MARSHALL-LERNER conditions are necessary and sufficient for a devaluation to be successful end are therefore the backbone of the elasticities approach to the balance of payments. These conditions are generalized by taking into account some actual features of modern foreign trade: positive import content of exports end the local content issue. In view of these effects, studied in a two country, two goods context, it can be concluded that a devaluation is likely to be less successful under given price elasticities. These results are of particular relevance for small open economies (SMOPECs).
Keywords: 330; Außenwirtschaftstheorie; Österreich